Less social emergency departments: implementation of workplace contact reduction during COVID-19. Issue 8 (24th June 2020) - Sangal, Rohit B; Scofi, Jean E; Parwani, Vivek; Pickens, Andrew T; Ulrich, Andrew; Venkatesh, Arjun K
Abstract : The COVID-19 pandemic has led to rapid changes in community and healthcare delivery policies creating new and unique challenges to managing ED pandemic response efforts. One example is the practice of social distancing in the workplace as an internationally recommended non-pharmaceutical intervention to reduce transmission. While attention has been focused on public health measures, healthcare workers cannot overlook the transmission risk they present to their colleagues and patients. Our network of three EDs are all high traffic areas for both patients and staff, which makes the limitation of close person-to-person contact particularly difficult to achieve. To design, implement and communicate contact reduction changes in the ED workplace, our COVID-19 task force formalised a set of multidisciplinary recommendations that enumerated concrete ways to reduce healthcare worker transmission to coworkers and to patients from ED patient arrival to discharge. We also addressed staff-to-staff contact reduction strategies when not performing direct patient care. We describe our conceptual approach and successful implementation of workplace distancing.